A study on framing strategies in trans-editing prison and inmate news - Liang, Xiaowen (Nanyang Technological University, 2021)
News coverage with the word “prisons” would naturally generate a negative ring as readers often associate it with topics on crime and punishment. However, as prisons are increasingly involved in rehabilitation efforts for the offenders, this pre-existing public perception of the prison organisation and by association, the concept of prisons and imprisonment, is gradually changing. Prisons-related news could be generalised into “hard news” and “soft news”; hard news usually induce negative perception and soft news on the contrary are relatively positive. Given the dichotomous nature of prisons-related news, this paper thus investigates framing strategies and the impact of public perception in trans-editing English news to Chinese. With a focus on the local news features of Singapore Prison Service’s statistics release in 2019, it was found that in Case Study 1, Chinese articles tend to employ episodic framing to draw readers’ attention and capitalised on emotional elements to generate positive public perception, through framing by reorganisation where paragraphs with human-interest contents were re-ordered as lead paragraphs instead. In examining the international news coverage on the passing of a death sentence over remote hearing in Singapore in Case Study 2, framing by substitution was predominant in trans-editing as foreign news agencies had substituted paragraphs detailing offence information with comments from activist groups criticising the cruelty of passing death penalty over remote hearing, changing the focus of the source articles. Framing by selective appropriation was common in both case studies: contents were added to showcase diversity in rehabilitation efforts as with Case Study 1, and to provide context to justify the remote hearing in Case Study 2; information was also omitted to reduce technicality in Case Study 1 and to neutralise the negative perception from heavily-opinionated views from activist groups in Case Study 2. Both cases attested to the political and cultural agenda motivating the act of trans-editing and framing strategies in news and media.